Aplicação de nanotubos de carbono no desenvolvimento de sensores amperométricos para compostos fenólicos - Cardoso, Rafael Melo (2016)
This work investigates the development of electrochemical sensors employing glassy-carbon electrodes modified with multi-walled carbon nanotubes (MWCNT). Two different diameters (110-170 nm x 5-9, μm corresponding to LD-MWCNT, and 6-9 nm x 5 μm, corresponding to SD-MWCNT), chemically treated with concentrated acids, subjected to amperometric and voltammetric analyses for the electrochemical oxidation of hydroquinone (HQ), tert-butylhydroquinone (TBHQ), catechol (CT), and pyrogallol (PY). The electrochemical response for all phenolic compounds in glassy-carbon electrode modified with nanostructured materials showed a small decrease in the overpotential of oxidation reactions (<80 mV). Furthermore, the values of ΔEpeak (distance between peak potential of the redox pair) were substantially reduced at LD-MWCNT and even more at SD-MWCNT compared to the unmodified electrode. Voltammetric tests showed a substantial increase (three fold) in oxidation current for the HQ, TBHQ, and PY on the modified electrode with SD-MWCNT. Amperometric measurements coupled to BIA system conducted in two different working potentials for each analyte also revealed the best performance of SD-MWCNT (increase up to four fold in sensitivity) for the detection of studied antioxidants, especially for the detection at lower potentials (0.5 V to HQ, TBHQ and PY and 0.6 V to CT). The analytical results obtained at lower potentials were respectively for HQ, TBHQ, CT and PY: large linear concentration ranges from 1 to 1000 μmol L-1; low limits of detection, 0.014 μmol L-1 / 0.011 μmol L-1/ 0.034 μmol L-1/ 0.013 μmol L-1; low relative standard deviation values, 0.9% / 3.5% / 1.3% / 2.8% , high theoretical analytical frequency, 1368,9 injections h-1 / 820,7 injections h-1 / 1018,7 injections h-1 / 987,9 injections h-1, employing the batch-injection analysis system. Moreover, an amperometric method for the determination of PY was developed and applied for biodiesel samples (produced from soybean, canola and cottonseed oils) spiked with the antioxidant, and recovery values of 95% were obtained.